David Antin : le poème, archive du monde contemporain - Hélène Aji (Sillages Critiques)
Considering the poetry of David Antin from the point of view of cumulative effect of the series of scripted and transcribed talk-poems, this article compares the published books by the author to an archival repository. Written in the continuous present, the poems perform the function of an archive, insofar as they outline the relevance of the past to the present, and allow for infinite reconfigurations. These reconfigurations are indexed to the contingency of place and time, both in historiographic and in poetic terms : they evidence the dynamics of the archive as distinct from the reactionary collection defined by Walter Benjamin and open the path to a thinking mode that crystallizes Urphänomene to address the present in ways that have been described by Hannah Arendt.